Effect of copper oxide nanoparticles on two varieties of sweetpotato plants - Bonilla Bird, Nestor J.; Flores Margez, Juan Pedro; Ye, Y.; Akter, T.; Valdes Bracamontes, C.; Darrouzet Nardi, A.J.; Saupe, G.B.; Ma, L.; Hernandez Viezcas, J.A.; Peralta Videa, J.R.; Gardea Torresdey, J.R. (2020)
Little information is available on the interaction of CuO nanoparticles (nCuO) with tuberous roots.In this study,Beauregard-14(B-14,lowlignin) and Covington COV,highlignin) sweet potato varieties were cultivated until maturity in soil amended with nCuO,bulk copper oxide(bCuO)andCuCl2at25–125mg/kg.TheCu treatments hadno significant influence on chlorophyll content.Gase xchangeparameterswerenotaffectedinB-14.InCOV,however,at125mg/kgtreatments,bCuO reducedtheintercellularCO2(11%),whileCuCl2increaseditby7%,comparedwithcontrol(p≤0.035).At25mg/kgnCuOincreasedthelengthofCOVroots (20.7 ± 2.0cmvs.14.6 ± 0.8cm,p≤0.05).InperidermofB-14,nCuO,at125mg/kg,increasedMgby232%,whiletheequivalentconcentrationofCuCl2 reducedPby410%,comparedwithcontrol(p≤0.05).ThedatasuggestthepotentialapplicationofnCuOasnanofertilizerforsweetpotatostoragerootproduction.